The process in Clinical Care Caritas' Jean Watson in Brazilian of nursing: a systematic review - Nirvania V. Carvalho; Dinah Sá Rezende Neta; Grazielle Roberta Freitas da Silva; Telma M. Evangelista de Araújo (Universidad de Alicante, 2012)
This systematic review aims at reviewing the implementation of Clinical Caritas processes, reformulation of the theory of human caring: Jean Watson, through published scientific papers. Only five products were found in the databases LILACS, SciELO, MEDLINE and BDENF after a rigorous application of inclusion judicious. The results showed that 80% of the publications are from 2006 and 60% performed at the South .The authors are post-graduate nurses who work in academy. The Clinical Caritas was applied in some areas of care in nursing, but there is a need for more productions to apply such an approach to care, yet little known, seeking to improve the of quality patient care and the community.